Distribution and Etiology of Mastitis in Cows, Economic Damage - Al-Rawashdeh O.O.A; Novikova E. N; Koba I.S (The Indian Veterinary Journal, 2024)
It has been established that mastitis is widespread in cow herds in the Krasnodar region. In 2014-2020, from 4.7 to 15.9% of cows were ill with mastitis. It has been established that the main etiological factor in the development of clinical mastitis is pathogenic and opportunistic microflora. Most often, microflora from the udder secretion is isolated in monoculture 52.6%, in association microflora is isolated in 39.7%. The most frequently isolated monocultures include staphylococci, including S. aureus (13.1%), E. agglomerans (13.1%), α and β hemolytic streptococci (13.2%), and E. coli (9.8%). Associations occur in the form of 2, 3, and 4 cultures of microorganisms.